2020
DOI: 10.1128/jvi.01299-19
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Cx n C Motifs in Kaposi’s Sarcoma-Associated Herpesvirus ORF66 Are Required for Viral Late Gene Expression and Are Essential for Its Interaction with ORF34

Abstract: Late gene transcription in the beta- and gammaherpesviruses depends on a set of virally encoded transcriptional activators (vTAs) that hijack the host transcriptional machinery and direct it to a subset of viral genes that are required for completion of the viral replication cycle and capsid assembly. In Kaposi’s sarcoma-associated herpesvirus (KSHV), these vTAs are encoded by ORF18, ORF24, ORF30, ORF31, ORF34, and ORF66. Assembly of the vTAs into a complex is critical for late gene transcription, and thus, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…However, studies are mostly restricted to the functional level due to low accumulation of vTFs and difficulties in their mechanism of study. Recent work in KSHV demonstrated that ORF66, the homolog of pM49, was essential for viral late gene expression via interaction between ORF34, the homolog of pM95 (31,32). Those studies, together with our results, provide a shred of evidence that the regulatory mechanism of viral late genes by vTFs is probably very conserved between betaherpesviruses and gammaherpesviruses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, studies are mostly restricted to the functional level due to low accumulation of vTFs and difficulties in their mechanism of study. Recent work in KSHV demonstrated that ORF66, the homolog of pM49, was essential for viral late gene expression via interaction between ORF34, the homolog of pM95 (31,32). Those studies, together with our results, provide a shred of evidence that the regulatory mechanism of viral late genes by vTFs is probably very conserved between betaherpesviruses and gammaherpesviruses.…”
Section: Discussionsupporting
confidence: 82%
“…pM49, pM95, pM79 and pM91 interacted directly or indirectly to form the core within the vTF complex; pM87 was thought to function as a hub to bridge pM92 and the core through the pM87-pM95 and pM87-pM92 interaction. Based on the research from Glaunsinger's group (31) and our references, we propose a hypothesis for the mechanism of the MCMV vTF transcription regulation system; we speculate that the members of the core complex, pM49, pM95, pM91, and pM79, may have the same role in viral late gene regulation. Although viral late gene expression regulatory mechanism remains largely unknown, it has been reported that the pM79 analog pUL79 serves as an elongation factor, but with no effects on RNA polymerase II (RNAPII) recruitment (28).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We assessed the ability of the NTD chimeras to functionally complement ORF24 using an established transfection-based late gene transcription assay [13][14][15]. The six vTAs (ORFs 18, 30, 31, 34, 66 and either WT ORF24, its homologs, or chimeras) were co-transfected into HEK293T cells, along with a firefly luciferase reporter controlled by the K8.1 late gene promoter or, as a control, the early ORF57 promoter.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…First, β/γ late gene transcription is regulated in part by a core promoter sequence 12-15 base pairs in length that has a TATT motif followed by a RVNYS motif in lieu of the canonical TATA box found in early viral promoters and in some cellular promoters [8][9][10][11]. Additionally, late gene expression requires at least six viral proteins, called viral transcriptional activators (vTAs), which form a complex at late gene promoters [12][13][14][15][16][17]. Little is known about the functional role these vTAs play in late gene transcription.…”
Section: Introductionmentioning
confidence: 99%